UNDERSTANDING BEHAVIOURAL BIASES IN INVESTMENT DECISION-MAKING: KEY DRIVERS AND IMPLICATIONS - Sana Begum M; Srinath, T.K (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study aims to explore the influence of behavioural biases on investment decisions. Utilizing a survey of 294 respondents, multiple regression analysis reveals that biases such as Anchoring and Representativeness, Overconfidence, Herd Behaviour, and Optimism significantly affect decision-making. Anchoring and Representativeness Bias emerges as the most influential factor, underlining the importance of cognitive heuristics. The findings provide practical implications for enhancing financial literacy and informed investment strategies while paving the way for future research on other biases and sector-specific variations.